2022
DOI: 10.3389/fmed.2022.890503
|View full text |Cite
|
Sign up to set email alerts
|

Using the Health Belief Model to Predict Vaccination Intention Among COVID-19 Unvaccinated People in Thai Communities

Abstract: BackgroundThe coronavirus disease 2019 (COVID-19) pandemic has become one of the biggest challenges to individual health and the public health system worldwide. COVID-19 morbidity and mortality are increasing, impacting almost every country including Thailand. This study used the Health Belief Model (HBM) as a framework to examine the intention of unvaccinated people living in northern Thailand to receive COVID-19 vaccines.MethodsThis cross-sectional study was conducted during October and November 2021. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The most typical preventive behaviors such as planning to get vaccinated, accepting vaccinations, wearing a face mask, keeping social distance, washing hands with soap and water, using hand sanitizer, self-quarantining, staying at home, not touching one’s face, and not going to public meetings. In this review, COVID-19 vaccine acceptance was positively correlated with all HBM constructs (perceived susceptibility, perceived severity, perceived barrier, perceived benefit, cues to action, and self-efficacy), 23 , 28 32 and constructs were also correlated with behavioral intention to engage in COVID-19 preventive behavior. 24 , 33 37 …”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…The most typical preventive behaviors such as planning to get vaccinated, accepting vaccinations, wearing a face mask, keeping social distance, washing hands with soap and water, using hand sanitizer, self-quarantining, staying at home, not touching one’s face, and not going to public meetings. In this review, COVID-19 vaccine acceptance was positively correlated with all HBM constructs (perceived susceptibility, perceived severity, perceived barrier, perceived benefit, cues to action, and self-efficacy), 23 , 28 32 and constructs were also correlated with behavioral intention to engage in COVID-19 preventive behavior. 24 , 33 37 …”
Section: Resultsmentioning
confidence: 80%
“…The most typical preventive behaviors such as planning to get vaccinated, accepting vaccinations, wearing a face mask, keeping social distance, washing hands with soap and water, using hand sanitizer, self-quarantining, staying at home, not touching one's face, and not going to public meetings. In this review, COVID-19 vaccine acceptance was positively correlated with all HBM constructs (perceived susceptibility, perceived severity, perceived barrier, perceived benefit, cues to action, and self-efficacy), 23,[28][29][30][31][32] and constructs were also correlated with behavioral intention to engage in COVID-19 preventive behavior. 24,[33][34][35][36][37] The application of TPB to COVID-19 preventive behaviors is based on 27 articles included in this systematic review, and the dimensions of TPB (attitude, social norm, and perceived behavioral control) were significantly associated with COVID-19 preventive behaviors.…”
Section: Application Of Behavioral Change Theory and Model On Covid-1...mentioning
confidence: 80%
See 2 more Smart Citations
“…Moreover, several studies have shown that the HBM constructs can serve as an important predictor of influenza vaccination uptake (Brewer et al, 2007; Shahrabani, Benzion & Yom Din, 2009; Shahrabani & Benzion, 2010; Tsutsui, Benzion & Shahrabani, 2012; Alsuwailem et al, 2023). During the COVID-19 pandemic, the HBM was used to assess the root causes of COVID-19 vaccine hesitancy in the Asia-Pacific region and beyond (Kabir et al, 2021; Alobaidi, 2021; Huynh et al, 2021; Zilhadia et al, 2022; Jian Ng et al, 2022; Shah et al, 2022; Seangpraw et al, 2022b,a; Limbu, Gautam & Pham, 2022b; Ghazy et al, 2022; Hidayana et al, 2022; Qin et al, 2022; Harutyunyan et al, 2023; Berger et al, 2023; Toledo-López et al, 2023).…”
Section: Introductionmentioning
confidence: 99%